Design and installation of (flower sun) a concentration dish and study its parameters - Yaseen. H. Mahmood; Abdl majeed.E.IbrahIm; Omar A .jadan (Tikrit Journal of Pure Science)
Design and installation of (3m) aperture concentration, by using Six curved pieces in the form of parabola Was covered by Aluminum golden mirror, the (focus) at (1.52 m) from the center of parabolic dish, a receiver (boiler) fixed at focus, the concentration ratio (37), we find the heat loss (29.780 W), and  the useful energy (1376.93W) and  the efficiency of the concentration 60 % at (500-750W/ ) the solar dish suitable  for solar application.